Suitability of using palm oil mill effluent as a medium for lipase production - Salihu, Aliyu; Alam, Md Zahangir; AbdulKarim, M. Ismail; Mohd. Salleh, Hamzah (Academic Journals, 2011)
Lipases are enzymes that can be secreted by several microorganisms using agro-industrial residues as potential substrates. This work screened ten microorganisms for their potential to produce lipase in palm oil mill effluent (POME)-based medium. Among the 10 organisms, the most promising strain was Candida cylindracea (ATCC 14830) which showed appreciable activity both on agar plates and liquid cultures. Medium supplementation by NH4Cl and olive oil led to an enzyme activity of 2.07 U/ml. However, supplementation with organic nitrogen sources resulted in better enzyme activity. Addition of malt extract, peptone and olive oil into the medium greatly influenced the lipase production. Among the oils that were tested, olive oil was found to be the best for the expression of extracellular lipase at 0.5% (v/v) with an activity of 4.02 U/ml in an optimized POME supplemented medium.